Ecological factors affecting minerals and nutritional quality of “Dryopteris filix-mas (L.) Schott”: an underutilized wild leafy vegetable in rural communities - Khan, Nasrullah; Ullah, Rafi; Okla, Mohammad K.; Abdel-Maksoud, Mostafa A.; Saleh, Ibrahim A.; Abu-Harirah, Hashem A.; AlRamadneh, Tareq Nayef; AbdElgawad, Hamada (Frontiers in Nutrition, 2024)
Dryopteris filix-mas (hereafter D. filix-mas), a wild leafy vegetable, has gained popularity among high mountain residents in the Hindukush-Himalaya region due to its exceptional nutritional profile, and their commercial cultivation also offers viable income alternatives. Nevertheless, besides phytochemicals with medicinal applications, ecological factors strongly affect their mineral contents and nutritional composition. Despite this, little has been known about how this wild fern, growing in heterogeneous ecological habitats with varying soil physiochemical properties and coexisting species, produces fronds with optimal mineral and nutritional properties. Given its nutritional and commercial significance, we investigated how geospatial, topographic, soil physiochemical characteristics and coexisting plants influence this widely consumed fern's mineral and nutrient content. We collected soil, unripe fern fronds, and associated vegetation from twenty-seven D. filix-mas populations in Swat, NW Pakistan, and were analyzed conjointly with cluster analysis and ordination. We found that the fronds from sandy-loam soils at middle elevation zones exhibited higher nitrogen contents (9.17%), followed by crude fibers (8.62%) and fats (8.09%). In contrast, juvenile fronds from the lower and high elevation zones had lower moisture (1.26%) and ash (1.59%) contents, along with fewer micronutrients such as calcium (0.14-0.16%), magnesium (0.18-0.21%), potassium (0.72-0.81%), and zinc (12% mg/kg). Our findings indicated the fern preference for middle elevation zones with high organic matter and acidic to neutral soil (pH ≥6.99) for retaining higher nutritional contents. Key environmental factors emerged from RDA analysis, including elevation (r = -0.42), aspect (r = 0.52), P-3 (r =0.38), K+ (r = 0.41), EC (r = 0.42), available water (r = -0.42), and field capacity (r = -0.36), significantly impacting fern frond's mineral accumulation and nutrient quality enhancement. Furthermore, coexisting plant species (r = 0.36) alongside D. filix-mas played a pivotal role in improving its mineral and nutritional quality. These findings shed light on the nutritional potential of D. filix-mas, which could help address malnutrition amidst future scarcity induced by changing climates. However, the prevalent environmental factors highlighted must be considered if the goal is to cultivate this fern on marginal lands for commercial exploitation with high mineral and nutrient yields in Hindukush-Himalaya.